Preparation method of TiB2 / 7050 aluminum-based composite material
By introducing flow-guiding ingots and controlling extrusion and pulling parameters in the preparation process of TiB2/7050 aluminum-based composite materials, the cracking and fracture problems of the material during deformation are solved, and the straightness and mechanical properties of the material are improved.
Patent Information
- Application Number
- CN202411879449.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
TiB2/7050 aluminum-based composite ingots are prone to cracking and breaking during deformation, and have poor plasticity, resulting in difficult extrusion deformation and poor straightness and mechanical properties.
The flow-guided ingot is used for flow-guided extrusion, and the relevant parameters are regulated during the extrusion and pulling process, including heating temperature, extrusion speed and tensile force, to ensure the stability and quality of the material during deformation.
It effectively avoids cracking and fracture problems of TiB2/7050 aluminum-based composite during the extrusion process, ensures the straightness and mechanical properties of the material, and improves the overall performance of the product.
Smart Images

Figure BDA0005204724130000071 
Figure BDA0005204724130000081 
Figure BDA0005204724130000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloys, and in particular to a method for preparing a TiB2 / 7050 aluminum-based composite material. Background Art
[0002] As a heat-treated aluminum alloy, aluminum-zinc-magnesium-copper alloy can regulate the dissolution and precipitation behavior of Cu, Zn, and Mg alloy elements in the aluminum matrix through solid solution-aging heat treatment, precipitate dispersed and fine alloy precipitation phases in the aluminum alloy, and significantly improve the strength of the aluminum matrix material. However, the elastic modulus of aluminum-zinc-magnesium-copper alloys is generally low, which cannot meet the requirements of major national projects for high specific stiffness and high specific modulus of metal structural materials.
[0003] The particle-reinforced aluminum-based composite material prepared by adding TiB2 ceramic particles into aluminum alloy, on the one hand, because TiB2 particles themselves have the characteristics of high hardness, high elastic modulus, low resistivity, low thermal expansion coefficient, etc., therefore, it can refine the grains, significantly improve the strength and modulus of the aluminum alloy, and improve the mechanical properties of the composite material; on the other hand, the introduction of semi-coherent TiB2 particles brings a large number of dislocations and lattice distortions to the interior of the aluminum grains. Such dislocations and lattice distortions caused by the introduction of the second phase can reduce the resistance of free electrons to move inside the grains, thereby improving the conductivity of the composite material; and through the coordinated regulation of subsequent processing deformation, heat treatment and other processes, the comprehensive performance of the product is further improved. Therefore, the TiB2 ceramic particle-reinforced aluminum-based composite material (TiB2 / 7050 aluminum-based composite material) has high specific strength and specific modulus, comparable to aluminum-lithium alloys, but the cost is 1 / 3 of that of aluminum-lithium alloys, showing incomparable performance of single aluminum alloys or polymer materials, enabling it to meet the needs of certain key components.
[0004] Compared with the ingots prepared by traditional melting and casting methods such as semi-continuous casting, the TiB2 / 7050 aluminum-based composite ingots prepared by powder metallurgy spray forming have the advantages of being able to cast ingots of larger specifications, dissolving more alloy elements and having almost no macro / micro segregation in the ingots. However, the spray-formed ingots have poor plasticity and exist pores. At the same time, the TiB2 / 7050 aluminum-based composite material has high specific strength and modulus and is difficult to deform, which leads to problems such as easy mold clogging or cracking and breakage of the extruded product during subsequent extrusion deformation. Furthermore, there is also the problem of not taking into account both straightness and cracking during straightening.
[0005] In summary, the plasticity of the powder injection-formed TiB2 / 7050 aluminum-based composite ingot is poor, and it is easy to crack during deformation processing; it has high strength, a large width-to-thickness ratio of the finished product, and is difficult to deform by extrusion, so it is easy to crack and block the mold during the extrusion process, and it is also easy to crack during the straightening process. Therefore, it is of great significance to provide a preparation method for TiB2 / 7050 aluminum-based composite materials to avoid cracking and ensure flatness and mechanical properties. Summary of the invention
[0006] The technical problem solved by the present invention is to provide a method for preparing a TiB2 / 7050 aluminum-based composite material. The preparation method provided by the present application can solve the problem of cracking or even breakage during the deformation process of the TiB2 / 7050 aluminum-based composite material ingot, while ensuring the flatness and mechanical properties of the aluminum-based composite material.
[0007] In view of this, the present application provides a method for preparing a TiB2 / 7050 aluminum-based composite material, comprising the following steps:
[0008] S1) heating the ingot and the TiB2 / 7050 aluminum-based composite material ingot to 390-430° C. respectively;
[0009] Heat the extrusion barrel of the extruder to 390-430°C, and heat the die of the extruder to 400-450°C;
[0010] S2) placing the heated ingot in an extruder for extrusion, and placing the heated TiB2 / 7050 aluminum-based composite material ingot in an extruder for extrusion when the extrusion of the ingot is not completed;
[0011] S3) quenching the extruded composite material;
[0012] S4) straightening the extruded material obtained in step S3) and then performing aging treatment;
[0013] The tensile forces of the straightening include 740-760t, 790-810t, and 840-860t in sequence.
[0014] Preferably, the diversion ingot is selected from 7xxx aluminum alloy ingots.
[0015] Preferably, in step S1), the flow-guided ingot and the TiB2 / 7050 aluminum-based composite material ingot are heated to 400-420° C. respectively, and the heating time is ≥600 min.
[0016] Preferably, in step S1), the extrusion barrel is heated to 400-420°C; and the mold is heated to 400-450°C.
[0017] Preferably, the timing of extruding the heated TiB2 / 7050 aluminum-based composite material ingot is when 1 / 3 of the heated ingot remains unextruded.
[0018] Preferably, the extrusion speed of the heated TiB2 / 7050 aluminum-based composite material ingot is 0.03-0.07 m / min, and the shaft speed is 0.05-0.10 mm / sec.
[0019] Preferably, the quenching temperature is 450-500°C, the holding time is 60-120 minutes, and the water temperature is 20-40°C.
[0020] Preferably, the stretching force of the straightening includes 750t, 800t, and 850t in sequence; the stretching amount of the straightening includes 0.8-0.9%, 1.0-1.1%, and 1.2-1.3% in sequence.
[0021] Preferably, the temperature of the aging treatment is 100-150° C., the holding time of the aging treatment is 12-36 hours, and the time for heating to the aging temperature is 2-3 hours.
[0022] Preferably, the straightening is performed within 2 hours after quenching.
[0023] The present application provides a preparation method of a TiB2 / 7050 aluminum-based composite material, which comprises firstly heating a flow-guiding ingot and a TiB2 / 7050 aluminum-based composite material ingot to 380-450°C respectively, and simultaneously heating an extrusion barrel of an extruder to 400-450°C, and heating a die of the extruder to 400-500°C, and then extruding the heated flow-guiding ingot first, and then performing flow-guiding extrusion on the composite material ingot, and then quenching the extruded composite material, and finally performing tension correction and aging treatment on the quenched extruded material, thereby obtaining a TiB2 / 7050 aluminum-based composite material. ; In the preparation process of TiB2 / 7050 aluminum-based composite materials, the temperatures of the guide ingot and the composite ingot are first controlled, and the temperatures of the extrusion barrel and the mold in the extruder are controlled at the same time to ensure the quality of the extruded material. The introduction of the guide extrusion method of the guide ingot during the extrusion process can effectively avoid the cracking and mold blocking of the composite ingot during the extrusion process; in the process of straightening, the present application simultaneously controls the tensile force of the straightening to ensure the straightness of the aluminum-based composite material while avoiding the cracking problem, and finally obtains an aluminum-based composite material with flatness that meets the requirements and excellent mechanical properties.
[0024] Furthermore, during the extrusion process, the present application adopts a matching extrusion ratio, extrusion temperature and extrusion speed, and cooperates with the diversion extrusion method to greatly improve the surface quality of the ultra-long TiB2 / 7050 particle reinforced aluminum-based composite material strip, effectively solving the problem of cracking or even breakage during the extrusion process. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A physical photo of a TiB2 / 7050 aluminum-based composite extrusion material with an ultra-large width-to-thickness ratio of 610*50mm prepared in Example 1 of the present invention;
[0026] Figure 2 This is a photo of the TiB2 / 7050 aluminum-based composite extrusion material with an ultra-large width-to-thickness ratio of 610*50mm prepared in an embodiment of the present invention after quenching;
[0027] Figure 3 This is a physical photo of the TiB2 / 7050 aluminum-based composite material prepared in the comparative example of the present invention. DETAILED DESCRIPTION
[0028] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0029] In view of the fact that the TiB2 / 7050 aluminum-based composite material in the prior art has poor plasticity of the ingot, is prone to cracking during deformation processing, and that the particle-reinforced aluminum alloy has high strength, a large width-to-thickness ratio of the material, is difficult to deform by extrusion, and is prone to cracking, the present application provides a method for preparing a TiB2 / 7050 aluminum-based composite material. The preparation method greatly improves the surface quality of the ultra-long TiB2 / 7050 particle-reinforced aluminum-based composite material by introducing a flow-guiding ingot and regulating the relevant parameters in the extrusion and straightening processes, effectively solves the problem of cracking or even fracture, and ensures the straightness and mechanical properties of the aluminum-based composite material. Specifically, the embodiment of the present invention discloses a method for preparing a TiB2 / 7050 aluminum-based composite material, comprising the following steps:
[0030] S1) heating the ingot and the TiB2 / 7050 aluminum-based composite material ingot to 390-430° C. respectively;
[0031] Heat the extrusion barrel of the extruder to 390-430°C, and heat the die of the extruder to 400-450°C;
[0032] S2) placing the heated ingot in an extruder for extrusion, and placing the heated TiB2 / 7050 aluminum-based composite material ingot in an extruder for extrusion when the extrusion of the ingot is not completed;
[0033] S3) quenching the extruded composite material;
[0034] S4) straightening the extruded material obtained in step S3) and then performing aging treatment;
[0035] The tensile forces of the straightening include 740-760t, 790-810t, and 840-860t in sequence.
[0036] In the preparation process of TiB2 / 7050 aluminum-based composite material, the present application first heats the diversion ingot and the TiB2 / 7050 aluminum-based composite material ingot to 390-430°C respectively; the diversion ingot can be used as long as it can realize diversion extrusion. In a specific embodiment, the diversion ingot is selected from 7xxx aluminum alloy ingots. There is no special restriction on the preparation method of the diversion ingot, and it can be prepared according to methods well known to those skilled in the art. There is no special restriction on the preparation method of the TiB2 / 7050 aluminum-based composite material ingot in this application, and it can be prepared according to methods well known to those skilled in the art. The heating temperature is specifically 400-420°C, and more specifically, the heating temperature is 400°C, 410°C or 420°C.
[0037] The present application heats the extrusion barrel of the extruder to 390-430°C and the die of the extruder to 400-450°C at the same time; the extrusion barrel and the die are heated to the above temperatures to prevent the composite material ingot from cracking due to a large temperature difference during the extrusion process. Specifically, the extrusion barrel is heated to 400-420°C and the die is heated to 410-440°C; in the embodiment, the heating temperature of the die is slightly higher than the heating temperature of the extrusion barrel.
[0038] According to the present invention, the heated flow-guided ingot is then placed in an extruder for extrusion. The extrusion process of the flow-guided ingot is carried out according to methods well known to those skilled in the art, and the present application has no particular restrictions on this. When the extrusion of the flow-guided ingot is not completed, the heated composite material ingot is placed in an extruder for extrusion. Specifically, when the remaining 1 / 3 of the flow-guided ingot is not extruded, the heated composite material ingot is placed in an extruder, and the composite material ingot is extruded on the basis of the extrusion of the flow-guided ingot. The extrusion speed is 0.01 to 0.15 m / min, and the shaft speed is 0.01 to 0.12 mm / sec; specifically, the extrusion speed is 0.03 to 0.07 m / min, and the shaft speed is 0.05 to 0.10 mm / sec; more specifically, the extrusion speed is 0.04 to 0.06 m / min, and the shaft speed is 0.06 to 0.08 mm / sec. The ingot casting guide pulls the TiB2 / 7050 aluminum-based composite ingot out of the extrusion equipment outlet, which can effectively avoid the ingot cracking and mold blocking during the extrusion process. At the same time, for the TiB2 / 7050 aluminum-based composite material with high specific strength and modulus and poor plasticity, the extrusion ratio, extrusion temperature (ingot insulation temperature, extrusion barrel constant temperature, mold temperature), and extrusion speed of the extrusion greatly affect the quality of the extruded product; selecting an appropriate extrusion ratio, controlling the extrusion temperature, reducing the extrusion speed, and doing a good job of front-end traction during the extrusion process can greatly improve the surface quality of the ultra-long TiB2 / 7050 particle-reinforced aluminum-based composite material strip, and effectively solve the problem of cracking or even breaking of the strip during the extrusion process.
[0039] The present application then quenches the extruded composite material to obtain a TiB2 / 7050 aluminum-based composite extrusion material; during this process, the quenching temperature is 450-500°C, the insulation time is 60-120 minutes, and the water temperature is 20-40°C; specifically, the quenching temperature is 470-490°C, and the insulation time is 80-100 minutes.
[0040] After quenching, the TiB2 / 7050 aluminum-based composite extrusion material will arch from the middle to both ends, and there will be a knife-bending phenomenon. Therefore, it is necessary to perform stretching and straightening within 8 hours of quenching, preferably within 2 hours; the stretching force of the stretching and straightening includes 740-760t, 790-810t, 840-860t in sequence, specifically, the stretching force includes 750t, 800t, 850t in sequence; the stretching amount includes 0.8-0.9%, 1.0-1.1%, 1.2-1.3% in sequence, specifically, the stretching amount includes 0.9%, 1.1%, 1.2% in sequence.
[0041] Finally, the composite material after straightening is subjected to aging treatment, the temperature of the aging treatment is 100-150°C, the insulation time of the aging treatment is 12-36h, and the time for heating to the aging temperature is 2-3h; specifically, the temperature of the aging treatment is 115-130°C, the insulation time is 12-24h, and the heating time is 2h.
[0042] In the present application, the TiB2 / 7050 aluminum-based composite material ingot includes: Si≤0.12wt%, Fe≤0.15wt%, Cu 2.0~2.8wt%, Mn≤0.10wt%, Mg1.90~2.80wt%, Cr≤0.04wt%, Zn 6.20~7.20wt%, Ti 2.70~4.50wt%, B1.0~2.0wt%, and the balance is Al.
[0043] Since the TiB2 / 7050 aluminum-based composite material has high specific strength and specific modulus and is difficult to deform, the TiB2 / 7050 aluminum-based composite material is prone to mold clogging during extrusion deformation, and may also suffer from cracking and breakage. In order to solve the above-mentioned problems of the TiB2 / 7050 aluminum-based composite material, the present application provides a preparation method of the TiB2 / 7050 aluminum-based composite material, which effectively avoids the occurrence of cracking or even breakage of the TiB2 / 7050 aluminum-based composite material by introducing a guide ingot for guided extrusion, and adapting the parameters before and during extrusion and in the straightening process, thereby ensuring the flatness and mechanical properties of the composite material.
[0044] In order to further understand the present invention, the preparation method of the TiB2 / 7050 aluminum-based composite material provided by the present invention is described in detail below in conjunction with the examples. The protection scope of the present invention is not limited by the following examples.
[0045] Example 1
[0046] The preparation of TiB2 / 7050 aluminum-based composite material strips with an ultra-large width-to-thickness ratio of 610*50mm includes the following steps:
[0047] (1) Extrusion process:
[0048] 11) Check the surface quality of the TiB2 / 7050 aluminum-based composite material ingot to ensure that the surface of the ingot is smooth and there is no oil stain, impurities or other foreign matter attached to the surface of the ingot;
[0049] 12) placing the 7xxx series aluminum alloy ingot and the TiB2 / 7050 aluminum-based composite ingot in an induction furnace for heating, the furnace temperature is set at 400-420° C., and the heating time is 600 min;
[0050] 13) The constant temperature range of the extrusion barrel is 400-420°C, and the mold heating constant temperature is 440-450°C;
[0051] 14) placing the heated ingot into a 12500T horizontal extruder and extruding it at a reasonable extrusion speed of the ingot, the extrusion speed is 0.7m / min, and the shaft speed is 1.23mm / s;
[0052] 15) When the remaining 1 / 3 of the ingot is not extruded, the heated TiB2 / 7050 aluminum-based composite material ingot is transferred for 10 minutes and then placed in the extruder, and the product speed is set to 0.05-0.06 m / min and the shaft speed is 0.08-0.09 mm / sec;
[0053] 16) Pay attention to the front end outlet of the extruded material. When the end of the guide alloy row pulls the TiB2 / 7050 alloy row out of the front end outlet of the extruder and reaches the traction equipment of the extruder, use the traction machine to pull it in time;
[0054] 17) After all the TiB2 / 7050 ingots are extruded, use 6xxx short ingots to push the material, apply more oil to the mold entrance section, push out the metal in the mold, and facilitate mold-material separation.
[0055] (2) Quenching process: Before quenching, drill a hole about 20 to 30 mm away from the head end of the extruded composite material. The quenching system is 480 ± 5 ° C / 90 min, the water temperature is 20 to 40 ° C, and the holding time starts when the temperature of the extruded composite material reaches 475 ° C.
[0056] (3) Straightening process: the quenched extruded material is stretched and straightened within 2 hours. The parameters of the stretching and straightening are shown in Table 1.
[0057] Table 1 Process parameters of tension straightening process
[0058]
[0059] (4) Aging process: The straightened composite material is subjected to aging treatment, and the aging treatment system is: 121±5℃ / 24h, and the heating time is 2h, to obtain TiB2 / 7050 aluminum-based composite material strips.
[0060] The edge quality of the extruded material prepared in this embodiment is good, and no obvious cracking is observed. Figure 1 shown.
[0061] The actual photo of the extruded material after quenching in this embodiment is as follows: Figure 2As shown in the figure, it can be seen that the extruded material after quenching is arched from the middle to both ends, and there is a knife bending phenomenon, so it is stretched and straightened afterwards; as can be seen from Table 1, the row of materials is intact after stretching and straightening, there is no cracking phenomenon, and the total length of the row of materials is 7m, the curvature and twisting degree are ≤4mm, which meets the straightness requirements.
[0062] The room temperature tensile properties of the TiB2 / 7050 aluminum-based composite material strip prepared in this embodiment were tested, and the results are shown in Table 2:
[0063] Table 2 Room temperature tensile properties of TiB2 / 7050 aluminum matrix composite materials
[0064]
[0065] As can be seen from Table 2, the tensile strength of different sampling positions of the TiB2 / 7050 aluminum-based composite material array prepared in this embodiment is greater than 620 MPa, the yield strength is greater than 550 MPa, and the elongation is greater than 5%, and the mechanical properties are excellent.
[0066] Comparative Example 1
[0067] The preparation method is the same as that of Example 1, except that: in the stretching and straightening step, the stretching and straightening parameters are shown in Table 3;
[0068] Table 3 Table of process parameters and effect data of the straightening process provided by comparative example 2
[0069] alloy Tensile force (t) Stretching amount (%) Stretching of material <![CDATA[TiB2 / 7050]]> 900 1.1 Cracked row material
[0070] Figure 3 This is a photo of the TiB2 / 7050 aluminum-based composite material strip prepared in this comparative example. As can be seen from the figure, the strip has cracks due to improper straightening process.
[0071] The composition of the TiB2 / 7050 aluminum-based composite ingot in the above examples and comparative examples is shown in Table 4;
[0072] Table 4 Composition data of TiB2 / 7050 aluminum matrix composite ingot
[0073]
[0074] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0075] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a TiB2 / 7050 aluminum-based composite material, comprising the following steps: S1) heating the ingot and the TiB2 / 7050 aluminum-based composite material ingot to 390-430° C. respectively; Heat the extrusion barrel of the extruder to 390-430°C, and heat the die of the extruder to 400-450°C; S2) placing the heated ingot in an extruder for extrusion, and when the extrusion of the ingot is not completed, placing the heated TiB2 / 7050 aluminum-based composite material ingot in an extruder for extrusion; S3) quenching the extruded composite material; S4) straightening the extruded material obtained in step S3) and then performing aging treatment; The tensile forces of the straightening include 740-760t, 790-810t, and 840-860t in sequence.
2. The preparation method according to claim 1, characterized in that: The diversion ingot is selected from 7xxx aluminum alloy ingots.
3. The preparation method according to claim 1, characterized in that: In step S1), the flow-guided ingot and the TiB2 / 7050 aluminum-based composite material ingot are heated to 400-420° C. respectively, and the heating time is ≥600 min.
4. The preparation method according to claim 1, characterized in that: In step S1), the extrusion barrel is heated to 400-420°C; the mold is heated to 400-450°C.
5. The preparation method according to claim 1, characterized in that: The timing for extruding the heated TiB2 / 7050 aluminum-based composite material ingot is when the remaining 1 / 3 of the heated ingot is not extruded.
6. The preparation method according to claim 1, characterized in that: The extrusion speed of the heated TiB2 / 7050 aluminum-based composite material ingot is 0.03-0.07 m / min, and the shaft speed is 0.05-0.10 mm / sec.
7. The preparation method according to claim 1, characterized in that: The quenching temperature is 450-500°C, the holding time is 60-120 minutes, and the water temperature is 20-40°C.
8. The preparation method according to claim 1, characterized in that: The stretching force of the straightening includes 750t, 800t, and 850t in sequence; the stretching amount of the straightening includes 0.8-0.9%, 1.0-1.1%, and 1.2-1.3% in sequence.
9. The preparation method according to claim 1, characterized in that: The temperature of the aging treatment is 100-150° C., the heat preservation time of the aging treatment is 12-36 hours, and the time for heating to the aging temperature during the aging treatment is 2-3 hours.
10. The preparation method according to claim 1, characterized in that: The tensile straightening is carried out within 2 hours after the quenching.